Effect of Good Corporate Governance, DER, Asset Growth Mechanism on Company Performance - Abdul Rahim; Kartika Mirawati; Juhasdi Susono (International Journal on Advanced Science, Education, and Religion, 2018)
This study aims to determine the effect of the mechanism of Good Corporate Governance, DER, Asset Growth on company performance (empirical studies on mining companies listed on the Indonesia, Thailand, Malaysia Stock Exchange period 2010-2017). This research is quantitative research which aims to systematically explain about the facts and properties in an object in the study then merged between variables related to it by presenting secondary data from financial reports from mining companies in the countries of Indonesia, Malaysia, and Thailand. The samples used in this study were 15 mining companies in the countries of Indonesia, Malaysia, and Thailand. In this study, the data analysis method used is the data panel (pooled data) which is a combination of time series data and data between individuals or cross sections in mining companies in Indonesia, Malaysia, and Thailand. This research indicates that the variation of the profit company's performance can be explained by the independent variables analyzed